« Bouter les anglicismes hors de France » - Léopold Julia (Lengas)
Are we (really) invaded by anglicisms? Defenders of the unilinguist ideology, language purists and conservatives, have never failed to alert us about the alleged dangers of borrowing from English. Wanting to answer this question in an objective and dispassionate way, my previous research led me to analyze the evolution of the rate of anglicisms among the new annual lexical entries in French dictionaries of use, over the last two decades. We will then try in this article, while keeping the prism of lexicometry, to propound a follow-up to this research by evaluating the effectiveness of the process meant for enriching the French language put in place by our institutions, in the deliberate aim of fighting precisely against these anglicisms. What if power was actually linguistic?